Germany (Country Survey) - Linke, Tibor; Leis, Theresia; Schönstedt, Jens; Yasar, Aysun; Nicolai, Katharina; Thielmann, Jörn (Yearbook of Muslims in Europe, 2024)

Germany (Country Survey) - Schönstedt, Jens; Leis, Theresia; Linke, Tibor (Yearbook of Muslims in Europe, 2025)

Turkish Mosque Archives in Industrial Towns in Southern Germany: An Ethnographic Survey - Jonker, Gerdientje; Elbel, Isabel; Klein, Arne; Klopke, Jule; Müssig, Stephanie; Schönstedt, Jens; Ulbricht, Victoria (Journal of Muslims in Europe, 2022)
Starting from the thesis that European mosque archives offer important sources for the history of Muslims and Islam in Europe, this contribution presents results of a pilot survey into the whereabouts of mosque archives in Germany. Focusing on five small towns in industrial zones where predominantly Turkish contract workers have settled, we asked Turkish mosque administrators, chairmen and imams how they had handled papers in the past, whether and where they had stored folders that were not in use anymore, and what kind of documents their collections contained. What we found were various archival records in a wide and unexpected range of places. We also learned that our questions prompted very different reactions. Umbrella organisations understood their archives as tools for preserving the written sources documenting their origins, whereas local administrators tended to see them as records of their personal memories. Our conclusion is that the time is ripe for the development of knowledge about mosque archives in Germany and, with regard to the founding generation, this is of crucial importance.
Created from Fastlane, Scopus look-up
Keywords: ethnographic survey; Germany; history of Muslims; mosque archives